Entry Regulation And Business Start-Ups : Evidence From Mexico - Kaplan, David S. (The World Bank, 2007)
The authors estimate the effect on business start-ups of a program that significantly speeds up firm registration procedures. The program was implemented in Mexico in different municipalities at different dates. Authors estimates suggest that new start-ups increased by about 4 percent in eligible industries, and the authors present evidence that this is a causal effect. Most of the effect is temporary, concentrated in the first 10 months after implementation. The effect is robust to several specifications of the benchmark control group time trends. The authors find that the program was more effective in municipalities with less corruption and cheaper additional procedures